Flipping the Metabolic Switch: Understanding and Applying the Health Benefits of Fasting - Anton, Stephen D.; Moehl, Keelin; Donahoo, William T.; Marosi, Krisztina; Lee, Stephanie A.; Mainous, Arch G.; Leeuwenburgh, Christiaan; Mattson, Mark P. (Obesity (Silver Spring, Md.), 2018)
Objective Intermittent fasting (IF) is a term used to describe a variety of eating patterns in which no or few calories are consumed for time periods that can range from 12 hours to several days, on a recurring basis. This review is focused on the physiological responses of major organ systems, including the musculoskeletal system, to the onset of the metabolic switch: the point of negative energy balance at which liver glycogen stores are depleted and fatty acids are mobilized (typically beyond 12 hours after cessation of food intake). Results and Conclusions Emerging findings suggest that the metabolic switch from glucose to fatty acid‐derived ketones represents an evolutionarily conserved trigger point that shifts metabolism from lipid/cholesterol synthesis and fat storage to mobilization of fat through fatty acid oxidation and fatty acid‐derived ketones, which serve to preserve muscle mass and function. Thus, IF regimens that induce the metabolic switch have the potential to improve body composition in overweight individuals. Moreover, IF regimens also induce the coordinated activation of signaling pathways that optimize physiological function, enhance performance, and slow aging and disease processes. Future randomized controlled IF trials should use biomarkers of the metabolic switch (e.g., plasma ketone levels) as a measure of compliance and of the magnitude of negative energy balance during the fasting period.